2010
DOI: 10.1159/000317429
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Plasma Levels in Patients with Idiopathic Short Stature

Abstract: Background: Novel molecular insights have suggested that ghrelin may be involved in the pathogenesis of some forms of short stature. Recently, growth hormone secretagogue receptor (GHSR) mutations that segregate with short stature have been reported. Aim: To study plasma ghrelin levels in prepubertal patients with idiopathic short stature (ISS). Methods: Fasting total plasma ghrelin levels (radioimmunoassay) in 41 prepubertal patients with ISS (18 females, age 7.9 ± 0.5 years) compared with 42 age- and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…It has been shown previously that short children tend to have increased ghrelin levels [31]. Therefore, not surprisingly, ghrelin levels were above the reference range in all study groups at baseline.…”
Section: Resultssupporting
confidence: 53%
“…It has been shown previously that short children tend to have increased ghrelin levels [31]. Therefore, not surprisingly, ghrelin levels were above the reference range in all study groups at baseline.…”
Section: Resultssupporting
confidence: 53%
“…We did so for several reasons. First, it was proved that in ISS AGA children, the ghrelin concentration is higher while IGF-I is lower than in controls [31,32]. In turn, in SGA children without catch-up growth who remain short, GH treatment improves final height [33] and brings about favourable long-term metabolic benefits [34].…”
Section: Discussionmentioning
confidence: 99%
“…e most prominent and early known effects of ghrelin following its discovery are appetite stimulation and GH release stimulation [7,58,59]. Nowadays, different studies showed that ghrelin has many functions beyond the initial discoveries ( Figure 3).…”
Section: System-based Understanding Of Physiological Effect Of Ghrelinmentioning
confidence: 99%